1998
DOI: 10.1097/00001756-199803300-00021
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis reduces neuronal apoptosis

Abstract: Acidosis is a well established concomitant of tissue ischemia. Acidosis in the pH range 6.0-7.0 is seen in cerebral ischemia and within solid tumors. Extracellular acidosis of pH 6.0 and 6.4 provided essentially complete protection from 48 h serum deprivation induced apoptotic death of cultured primary murine neurons. We tested the effect of p53 using transformed mouse embryo fibroblasts of either p53+/+ or p53-/- genotype. Both were markedly protected from serum deprivation by acidity. Hypoxia induced fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 10 publications
3
23
0
1
Order By: Relevance
“…1 This result has later been confirmed by another study that showed the protective effect of acidification on pulmonary artery endothelial cell death triggered by metabolic inhibition 2 and is in agreement with another prior report that has shown comparable results in hepatic sinusoidal endothelial cells. 3 Similar results on the protective effect of low pH have also been obtained in other cell types, including neurons, 4 hepatocytes, 5 myocardiocytes, 6 and some tumor cells, 7 kept under conditions of serum deprivation or hypoxia to induce apoptosis. Furthermore, it has been shown that repetitive brief episodes of acidification protect the heart from subsequent ischemic injury.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…1 This result has later been confirmed by another study that showed the protective effect of acidification on pulmonary artery endothelial cell death triggered by metabolic inhibition 2 and is in agreement with another prior report that has shown comparable results in hepatic sinusoidal endothelial cells. 3 Similar results on the protective effect of low pH have also been obtained in other cell types, including neurons, 4 hepatocytes, 5 myocardiocytes, 6 and some tumor cells, 7 kept under conditions of serum deprivation or hypoxia to induce apoptosis. Furthermore, it has been shown that repetitive brief episodes of acidification protect the heart from subsequent ischemic injury.…”
supporting
confidence: 70%
“…Nevertheless, the results of the present study provide a working hypothesis to explain the antiapoptotic effect of acidification observed in a variety of cell types and experimental conditions. 1,2,4,6,7,[35][36][37] Endothelial cells are exposed to low pH in many conditions, including ischemia and metabolic or respiratory acidosis, 38 exposure to drugs that inhibit Na ϩ -H ϩ exchange in the plasma membrane, 2 and laminar shear stress, 39 which also has a marked antiapoptotic effect on these cells. 34 Finally, because Gas6/Axl signaling may be activated by low pH in other cell types also, a potential role for this pathway may be considered in ischemic preconditioning of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells are also exposed to low pH, increased pressure, lack of glucose or serum, and osmotic shock (32,33). It is therefore possible that these factors have a co-operative role in inducing the phosphorylation of ATR targets like p53 serine 15 or histone H2AX.…”
Section: Resultsmentioning
confidence: 99%
“…In hypoxic neuronal cultures extracellular acidity in the range 6.0-7.0 has been found by some to reduce both apoptosis (Xu et al 1998) and NMDA receptor-mediated toxicity (Giffard et al 1990), while others have found it to either augment AMPA-kainate receptor-mediated toxicity (McDonald et al 1998), or simply be injurious instead of protective (Ding et al 2000). It is possible that extracellular pH values in our slices were lower than pH i values in the better buffered intracellular space, and therefore outside the ranges used in other studies.…”
Section: Nmr Detection Of Energy Restoration During Apoptosismentioning
confidence: 99%